(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Foramen magnum meningiomas are challenging tumors, requiring special considerations because of the vicinity of the medulla oblongata, the lower cranial nerves, and the vertebral artery. After detailing the relevant anatomy of the foramen magnum area, we will explain our classification system based on the compartment of development, the dural insertion, and the relation to the vertebral artery. Method: A 35 years age lady with foramen magnum meningioma was operated at the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University 6 months back. A case report was taken before surgery and 6 month follow up was done after operation. Conclusion: As foramen magnum meningioma is very difficult to approach, with the help of microscope with proper training. We can remove completely without any deficit. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21031